Uji Performa Gasoline Engine menggunakan bioaditif cengkeh dengan bensin berkadar oktan 90 - Devia Gahana Cindi Alfian; Rico Aditia Prahmana; Dicky J. Silitonga; Abdul Muhyi; Didik Supriyadi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2020)
Globally, the demand for fuels is ever-increasing and so is the demand for fuel additives. A fuel additive is a substance added in small quantities to increase the performance of the engine, decrease fuel consumption and reduce emission. The fuel additives have no specific set of raw materials or ingredients. Every fuel additive is different from the other in many ways of raw materials and ingredients to produce these additives. In many cases, fuel additives have made by chemical materials as additives for a gasoline engine. However, the optimal parameters for the reduction of fuel consumption are not clear. Accordingly, the present study performs a mixing additive material in the form of clove oil with pure gasoline fuel with a percentage of 1%, 0,6% and 0,3% from a total volume of gasoline to be tested. Then the mixing of the additive and gasoline is tested into the gasoline engine by varying the load using 200, 400, 600, 800, 1000, 1200, 1400, 1600, 1800 and 2000 Watt power with a fixed engine rotation of 2500 rpm. The results show that the reduction of fuel consumption respectively. Results showed that the addition of 1%, 0.6% and 0.3% clove oil into a 90 octane gasoline reduced fuel consumption by 10.6%, 18.2% and 15.4% respectively. Maximum reduction of fuel consumption was 28.6% at 800 W electrical load with 0.6% of clove oil additive.